Harvesting ETD Metadata from Institutional Repositories to OCLC: Approaches and Barriers to Implementation. Issue 2 (2nd April 2016) - Veve, Marielle
Abstract : This article discusses some of the most popular automated and semi-automated approaches currently used in libraries to harvest electronic theses and dissertations' (ETD) metadata from institutional repositories (IR) to the Online Computer Library Center (OCLC). The approaches presented are divided into four main sections: (1) completely automated approaches, (2) semi-automated approaches that rely on ProQuest Services, (3) semi-automated approaches that rely on highly technical tools, and (4) semi-automated approaches that rely on the MarcEdit OAI Harvester. An analysis, including limitations and barriers to implementation, is provided and solely based on case studies presented throughout the library literature, on presentations, and on the author's and other institutions' experiences. Recommendations for future research and suggestions for improvements are provided.